Careers Where the Jobs Are. - Cass, Stephen (IEEE spectrum)
IEEE Spectrum teamed up with The New York Times to survey 752 IEEE members about the past, present, and future technological trends they are seeing. Rather than looking at industry statistics such as sales or market values, this paper focused on tracking research and development efforts across 19 technological areas as well as academia. This focus was chosen because, apart from the fact that R&D is specifically the work many engineers do to earn their living, R&D staffing and spending act as a general bellwether: declining investment in R&D typically indicates an area that isn't set for high growth or is experiencing commoditization of its products and the attendant squeezing of profit margins